Coloration and Nonlinear Optical Properties of ZnTe Quantum Dots in ZnO–TeO2–P2O5 Glasses. Issue 1 (13th December 2013) - Du, Xi; Zhang, Liaolin; Dong, Guoping; Sharafudeen, Kaniyarakkal; Wen, Jian; Chen, Dongdan; Qian, Qi; Qiu, Jianrong
Abstract : ZnO–TeO2 –P2 O5 glasses were prepared by melt‐quenching method. The color of the glass samples changed from colorless to pale red and dark red with increasing TeO2 content. Coloration mechanism and nonlinear optical properties of ZnO–TeO2 –P2 O5 glasses have been investigated. Raman spectra and transmission electron microscope measurements indicated the precipitation of ZnTe quantum dots in the glasses and ZnTe quantum dots are the origin of coloration. Z‐scan technique was used to examine the nonlinear optical properties of the glasses. The glass sample with 30 mol% TeO2 exhibits large third‐order nonlinear optical susceptibility of 10 −11 esu.